Using blockchain to authenticate luxury products: a stakeholder perspective - Bonin, Paul Nicolas Antoine (2023)
Blockchain technology has emerged as a promising solution to combat counterfeiting and enhance authenticity in the luxury industry. It offers secure digital certificates of ownership, ensuring product genuineness and traceability, ultimately benefiting both manufacturers and customers. However, challenges include data privacy concerns, technical issues, scalability limitations, and customer awareness. Successful blockchain adoption in the luxury sector requires overcoming these hurdles and striking a balance between costs and benefits. Therefore, this study aims to investigate the added value brought by blockchain authentication for both customers and brands, to better understand if implementing blockchain authentication is valuable for luxury stakeholders on a broad scale. After studying the relevant literature, this study examines two luxury blockchain consortiums to understand how they solve the abovementioned problems and unlock added value for both luxury brands and customers. The research method used is the case study method, enriched with interviews of luxury experts and customers. It was found that, on the customer side, blockchain unlocks value by providing product supply chain information, easily verifiable and transferable proof of authenticity and ownership, and a reliable item lifecycle register. For brands, blockchain could become a single source of truth for supply chain stakeholders, guarantee compliance with environmental and social standards, on top of allowing item traceability after purchase, and unlock new customer engagement opportunities. This research aims to study the added value of blockchain luxury item authentication for both brands and customers and bridge the gap between the operations-related literature and the marketing-related one.